2016
DOI: 10.1016/j.ijsu.2016.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection in the elderly: A retrospective cohort study of 460 patients – Feasible and safe

Abstract: Age alone should not be a contraindication for liver resection. However, elderly patients who develop pneumonia are at high risk for postoperative mortality. Therefore, factors such as short time of invasive ventilation, direct and intensive respiratory therapy and mobilization are of particular importance and should be focused on even more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…However, according to the literature, we have an increased rate of reoperation (9 vs. 5%) without postoperative mortality. Elderly patients did not have a higher rate of postoperative cardiopulmonary complications as also shown by Andert et al [17] in a retrospective cohort study of 460 elderly patients who underwent liver ­resection.…”
Section: Discussionsupporting
confidence: 58%
“…However, according to the literature, we have an increased rate of reoperation (9 vs. 5%) without postoperative mortality. Elderly patients did not have a higher rate of postoperative cardiopulmonary complications as also shown by Andert et al [17] in a retrospective cohort study of 460 elderly patients who underwent liver ­resection.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies reported that liver resection via the open approach in the elderly (65 to 70 years) was very high mortality range from 3.5 to 5.6% [14, 15]. However, our results showed zero perioperative mortality rate of LH in elderly, which may associate with decreased blood loss and decreased surgical wall trauma with laparoscopic approach.…”
Section: Discussioncontrasting
confidence: 46%
“…Some authors describe liver surgery in elderly patients as safe as in young [9, 19]. Others see slightly higher morbidity or mortality rates with especially postoperative pneumonia as a risk factor for mortality [20, 21]. Tufo and colleagues were able to show that the number of patients who underwent liver resection older than 70 years raised from 6% in 1990 to > 25% in 2007 [18].…”
Section: Discussionmentioning
confidence: 99%